THE SPIRITUAL DIMENSION AS A KEY ASPECT OF THE POETICS OF THE “THE CATASTROPHE” NOVEL BY V. DRIZD - Lytvyn, N. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to the problem of the “spiritual thirst” of an individual in a socialist society, which was mentioned by V. Drizd in his first novel called “The Catastrophe”. The features of author’s comprehension of the spiritual dimension of the so-called “distorted” personality are considered. The manifestations of the spiritual dimension as a key and functional component of the poetics of the artistic-shaped plane of the text are analyzed. The main means (autobiography, anthroponomy, internal speech, portrait and its details) are distinguished, which determined the artistic quality of the “The Catastrophe” novel.